Determinan Tax Avoidance Pada Industri Barang Konsumsi Tahun 2014-2018 - Elvina Dwi Anita; Kartika Hendra Titisari; Siti Nurlaela (Ekonomis: Journal of Economics and Business, 2020)
Taxes are the country's biggest income support but are against the interests of companies that consider taxes to be a deduction from income. Differences in interests have caused many tax avoidance cases to minimize tax payments. The purpose of this study was to analyze the influence of independent commissioners, audit committees, capital intensity, leverage, profitability, and advertising costs on tax avoidance. The consumer goods industry on the Indonesia Stock Exchange in the 2014-2018 period, 38 companies were made into populations. The use of a purposive sampling technique produced 23 sample companies with 115 observational data. The data analysis technique uses panel data regression with selected random effect models. The results of the study prove that leverage and profitability affect tax avoidance, while independent commissioners, audit committees, capital intensity, and advertising costs do not show an effect on tax avoidance.